Finite element analysis of interference fit considering geometrical form errors - Ei Shwe Sin Win (2012)
Interference fitted connections are widely used in the assembly of two cylindrical parts which are either shrink fitted or press fitted. They are commonly used in assembly between shaft and bearings and gears and collars. There have been many analyses of interference fit in the literature. This will be elaborated detail in chapter 2.